Macroeconomic Determinants of GDP Growth in Nepal: A Study on Remittances, Inflation, and Foreign Direct Investment - Khadka, Arjun Bikram; Mishra, Uttam; Mishra, Udgam (Journal of Research and Development, 2025)
This research aims to explore the contribution of remittance, inflation, and foreign direct investment (FDI) to GDP growth in Nepal from 2000 to 2023. Remittance inflows constitute a large portion of the Nepalese economy, but their contribution to long-term GDP growth is not well understood. Inflation consistently poses a challenge, compounded with price shocks and intrinsic structural weaknesses. Despite its insignificance, FDI is considered a source of future economic growth. Adopting a quantitative approach with a toolset consisting of descriptive statistics, correlation analysis, and multiple regressions, in an investigation of causality between these and GDP growth, the analysis identifies poor correlations between GDP growth and remittance inflows and between inflation and GDP growth, and a positive, yet poor, one with FDI. The outcomes of a modeled regression, in terms of factors contributing towards GDP growth, reveal them to contribute towards explaining little variance, necessitating considerable interventions in terms of policy in such a scenario. Thus, it is advised that such policies must be adopted in an attempt to direct remittance inflows towards productive sectors, manage inflation through monetary intervention, and promote governance structures in an attempt to draw in FDI, guided through the observations in this analysis.